Articulation, language and reading skills of Filipino children with dyslexia - Ynion, Ma. Rowena Arao (2007)
Dyslexia is one of the most common causes of reading and writing difficulties in children. This study investigated the different articulation, language and reading skills of school-aged children diagnosed to have dyslexia. The participants in this study were twenty students attending Grade 2 to 4 classes at Worldlab School in Manila. They were given a battery of tests that measured listening comprehension, articulation, and language skills. This study confirmed the observation that children with dyslexia generally do not exhibit any articulation problems, provided further evidence to language-based difficulties, indicating that Filipino students with dyslexia generally performed better in decoding in isolation and spelling than in vocabulary, reading comprehension, and oral reading fluency.
"March 2007."
Thesis (M.A. Reading Education)--University of the Philippines Diliman.
Keywords: Dyslexic children -- Education -- Philippines -- Manila Metropolitan Area; Dyslexia -- Philippines -- Manila Metropolitan Area; Reading (Primary) -- Philippines -- Manila Metropolitan Area